2010
DOI: 10.26719/2010.16.7.778
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection in 755 patients with digestive complaints: Pasteur Institute, Morocco, 1998-2007

Abstract: We determined the prevalence of Helicobacter pylori infection in 755 patients with digestive complaints identified from laboratory records at the Pasteur Institute, Morocco from 1998 to 2007. Epidemiological factors and gastrointestinal conditions associated with this infection were also studied. All patients underwent endoscopy and diagnosis was by histology examination. The prevalence of H. pylori infection was 69%. The difference in prevalence between the age group 40-50 years and other age groups was stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
7
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
5
7
1
1
Order By: Relevance
“…pylori in 71.73% of our population. The same results were found by Attaf et al [ 36 ] which attributed 70.9% of lesions to this site, and Joutei et al [ 32 ] with 73%. In another study, these values remain higher than those reported by Binan et al [ 37 ] who attributed 40.0% of H .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…pylori in 71.73% of our population. The same results were found by Attaf et al [ 36 ] which attributed 70.9% of lesions to this site, and Joutei et al [ 32 ] with 73%. In another study, these values remain higher than those reported by Binan et al [ 37 ] who attributed 40.0% of H .…”
Section: Discussionsupporting
confidence: 87%
“…pylori infection by age, we obtained a peak rate (71.43%) affecting the ‘60–69’ age group. This average is higher than those found by Joutei et al [ 32 ], which revealed a rate of 11% among subjects in the ‘60–70’ age groups. For Ivorian, no significant difference has been reported for age groups [ 33 ].…”
Section: Discussioncontrasting
confidence: 74%
“…Four studies were reported from Africa [16–19]. Studies from Africa recorded high H. pylori prevalence rates ranging from 41.3% to 91.3% [16–19].…”
Section: Prevalencementioning
confidence: 99%
“…Four studies were reported from Africa [16–19]. Studies from Africa recorded high H. pylori prevalence rates ranging from 41.3% to 91.3% [16–19]. There were seven studies that reported H. pylori prevalence from South America [20–26].…”
Section: Prevalencementioning
confidence: 99%
“…L'HP induit une gastrite atrophique entraînant la destruction des cellules pariétales qui produisent le facteur intrinsèque. L'infection à HP est plus élevée dans les pays en voie de développement (78 % en Algérie, 71 % au Maroc, 69 % en Côte d'Ivoire) [11], il est logique de penser que la carence en vitamine B12 et ses conséquences soient plus importantes. La gastrite atrophique à HP est une cause fréquente du syndrome de non-dissociation de la vitamine B12 [10].…”
Section: Figureunclassified